2021
DOI: 10.2147/nss.s316113
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Sleep as Compensation for the Effects of Reduced Nocturnal Sleep on the Incidence of Hypertension: A Cohort Study

Abstract: The role of sleep duration in the development of hypertension remains controversial. Little is known about the combined effects of nocturnal and daytime sleep. We assessed the association between total sleep duration and the development of hypertension in middle-aged and elderly Chinese adults. Patients and Methods: Data were obtained from 3 waves of China Health and Retirement Longitudinal Study surveys. Middle-aged and elderly Chinese initially without hypertension were followed biennially from 2011 to 2015.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
1
3
0
2
Order By: Relevance
“…Our study concluded that insufficient sleep was associated with an increased risk of hypertension, which was consistent with the results of most previous studies [1,2,3,6,7,8,[12][13][14][15]. However, our results demonstrated that participants with only a short (<6 h/day) sleep duration had a greater risk of hypertension, while a long (>8 h/day) sleep duration did not significantly increase the risk of hypertension.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study concluded that insufficient sleep was associated with an increased risk of hypertension, which was consistent with the results of most previous studies [1,2,3,6,7,8,[12][13][14][15]. However, our results demonstrated that participants with only a short (<6 h/day) sleep duration had a greater risk of hypertension, while a long (>8 h/day) sleep duration did not significantly increase the risk of hypertension.…”
Section: Discussionsupporting
confidence: 92%
“…However, there have been clear discrepancies among the findings of these studies. Certain studies found that both short and long sleep durations were associated with an increased risk of hypertension [1,2,13,14], while several studies only identified a short sleep duration as associated with an increased risk of hypertension [3,6,7,8,12,15], and yet other studies denied this association [5,11,17]. The objective of the current study was to evaluate the association between self-reported sleep duration and hypertension among adults in southwest China.…”
Section: Introductionmentioning
confidence: 94%
“…Heterogeneity was measured using I 2 statistics [ 22 ]. We conducted a sub-group analysis to evaluate the relationship between sleep duration and risk of HTN incidence after stratification according to the different definitions of short (< 5 hours, 5 to 7 hours) [ 23 25 ] and long (8 to 9 hours, and > 9 hours) [ 23 , 24 , 26 ] sleep durations and different durations of follow-up (< 5 years and >5 years), in instances where I 2 surpassed 50%. Potential publication bias was evaluated via funnel plot asymmetry, Egger’s regression, and the Begg tests [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Acredita-se que a curta duração do sono noturno ou a sua baixa qualidade foi compensada pelo sono diurno, o que pode ter atenuado os resultados adversos à saúde. Essa interpretação foi corroborada em outra investigação, que destaca, ainda, que o sono diurno habitual pode reduzir o risco de incidência de HAS de forma independente, conforme resultados de um estudo de coorte (27) . Destarte, o ritmo circadiano, como relógio fisiológico, é um biomarcador natural da relação entre vigília e repouso, sendo que o natural é a ocorrência de uma vigília diurna e de um repouso noturno, com duração aproximada de oito horas/noite.…”
Section: Eu Durmo Em Média Três Horas Por Noite Isso Quando Durmo O Q...unclassified
“…Sendo assim, a compensação diurna do sono pode, portanto, desempenhar um importante papel na prevenção da HAS em adultos e idosos que conseguem dormir por curtos períodos durante a noite. Nesse sentido, o "cochilo" diurno pode melhorar o estresse neuroendócrino e a recuperação imunológica, com potencial efeito profilático na saúde cardiovascular em longo prazo (27)(28) .…”
Section: Eu Durmo Em Média Três Horas Por Noite Isso Quando Durmo O Q...unclassified